Performance Test of the Molecularly Imprinted Polymer (MIP) Endosulfan Sensor Potentiometrically - Bow, Yohandri; Syakdani, Adi; Purnamasari, Indah; Rusdianasari (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
Molecularly Imprinted Polymer (MIP) is a synthetic polymer with cavities that are specific for target molecules. Cavities are obtained as a result of template removal, where the function of these cavities is to recognize molecules with the same size, structure and physicochemical properties as them. The polymer produced from the MIP technique is applied to the surface of the sensor material as an endosulfan detection and analyzing instrument. The advantage of MIP is that it is a sensor system that is able to provide analysis results for contamination quickly, easily and in low concentrations (ppm). The aim of this research is to make MIP endosulfan as a contamination sensor and potentiometrically test its performance. The research results showed that the optimum conditions for making Molecularly Imprinted Polymer (MIP) endosulfan were obtained with a composition of 6.02 mL of chloroform; endosulfan 0.025 g; 0.9 mL methacrylic acid (MAA); 1.57 mL ethylene glycol methacrylic acid (EGMA); 0.07 g benzoyl peroxide (BPO) with a heating time of 150 minutes at a temperature of 70 oC. The sensor performance test was carried out potentiometrically and it was found that the endosulfan MIP sensor had sensitivity and stability in the concentration range of 0.01-1.0x10-6 ppm with a detection limit of 0.01x10-6 ppm and a service life of 90 days.